Endurance Training in Normobaric Hypoxia Imposes Less Physical Stress for Geriatric Rehabilitation - Pramsohler, Stephan; Burtscher, Martin; Faulhaber, Martin; Gatterer, Hannes; Rausch, Linda; Eliasson, Arn; Netzer, Nikolaus C. (Frontiers in Physiology, 2017)
Rationale: Evidence suggests that training in hypoxia can be very effective even while requiring less physical effort. We therefore aimed to measure the effect of endurance training under hypoxic conditions on pulmonary and cardiovascular parameters in an elderly population undergoing inpatient rehabilitation. Methods: Forty patients over age 65 years with multiple co-morbid conditions were recruited during a 3-week stay in a geriatric rehabilitation center. Using a randomized, single-blinded, placebo-controlled design, patients were assigned to a hypoxic (HG) or normoxic (NG) group. HG patients completed seven training sessions of 30 min duration on a treadmill in a normobaric chamber with inspired oxygen fraction (FiO2) of 15.27%, with 10–30 min active training. Training was conducted with target heart rate at 80% of peak oxygen consumption (VO2-peak). NG group performed similar training in sham hypoxia (room air or FiO2 = 20.94%). At pre- and post-test completion, measures included: (1) cycle ergometry with ECG monitoring and measurement of VO2-peak, and (2) echocardiography for ejection fraction. Results: The physical effort required of patients to reach target heart rate was reduced significantly (−28%, p = 0.043) in the HG compared to NG. Cardiopulmonary parameters showed no differences between groups. Conclusion: Endurance training at 3,000 meters elevation imposes less stress on the locomotor systems while resulting in a similar physiological strain (i.e., heart rate). Hypoxic training holds promise for successful geriatric rehabilitation by being more accommodating to physical limitations in geriatric patients. Trial registration: Registration at DRKS. (Approval No. 359/12, Trial No. DRKS00005241).